The Protein Phosphatases ATUNIS1 and ATUNIS2 Regulate Cell Wall Integrity in Tip-Growing Cells. Issue 8 (10th July 2018) - Franck, Christina Maria; Westermann, Jens; Bürssner, Simon; Lentz, Roswitha; Lituiev, Dmytro Sergiiovych; Boisson-Dernier, Aurélien
Abstract : The serine/threonine protein phosphatases ATUNIS1 and ATUNIS2 function downstream of CrRLK1Ls to negatively regulate cell wall integrity during tip growth. Abstract: Fast tip-growing plant cells such as pollen tubes (PTs) and root hairs (RHs) require a robust coordination between their internal growth machinery and modifications of their extracellular rigid, yet extensible, cell wall (CW). Part of this essential coordination is governed by members of the Catharanthus roseus receptor-like kinase1-like ( Cr RLK1L) subfamily of RLKs with FERONIA (FER) and its closest homologs, ANXUR1 (ANX1) and ANX2, controlling CW integrity during RH and PT growth, respectively. Recently, Leucine-Rich Repeat Extensin 8 (LRX8) to LRX11 were also shown to be important for CW integrity in PTs. We previously reported an anx1 anx2 suppressor screen in Arabidopsis thaliana that revealed MARIS (MRI) as a positive regulator of both FER- and ANX1/2-dependent CW integrity pathways. Here, we characterize a suppressor that exhibits a weak rescue of the anx1 anx2 PT bursting phenotype and a short RH phenotype. The corresponding suppressor mutation causes a D94N substitution in a Type One Protein Phosphatase we named ATUNIS1 (AUN1). We show that AUN1 and its closest homolog, AUN2, are nucleocytoplasmic negative regulators of tip growth. Moreover, we demonstrate that AUN1 D94N and AUN1 H127A harboring mutations in key amino acids of the conserved catalytic site of phosphoprotein phosphatases function as dominant amorphic variants that repress PT growth. Finally, genetic interaction studies using the hypermorph MRI R240C and amorph AUN1 D94N dominant variants indicate that LRX8-11 and ANX1/2 function in distinct but converging pathways to fine-tune CW integrity during tip growth.